(untitled) (Revista de Psicología, 2024)
This essay raises and defends the thesis that some of the contemporary developments in the historical-cultural approach are of great relevance to education and pedagogical practices, in particular the elaborations of the learning-development relationship as conceptualized by Vygotsky. Based on research conducted by the author, its objective is to provide information on the background of these developments, discuss and analyze them, and share reflections regarding their implications. The approach to the topic is carried out through a critical review of contemporary academic literature that elaborates some ideas and produces research inspired by the legacy of L.S. Vygotsky. Consistent with the historical-cultural approach, the examination of contemporary theoretical and investigative productions begins by establishing their background and contextualizing them. The analysis results in a complex perspective in which concepts relegated in readings and interpretations of Vygotsky’s work come to occupy a central place. It is concluded that from this place proposals have been generated and continue to be generated to transform traditional education into a practice oriented towards equity and social justice.